PENGARUH JARAK TANAM DAN APLIKASI PUPUK HAYATI MIKORIZA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (Vigna radiata L.) PASCA PADI - Dwi Ayu Sunarti; Wayan Wangiyana; Nihla Farida (Agros Journal of Agriculture Science, 2024)
Mungbean plants (Vigna radiata L.) are reported to be able to form a symbiotic relationship with Rhizobium bacteria and arbuscular mycorrhizal fungi (AMF) to increase grain yield. This research aims to determine the effect of planting distance and application of mycorrhiza biofertilizer on growth and yield of mungbean planted a paddy field following rice crop. The experiment was carried out at the Unram Farming, Narmada and the Microbiology Laboratory, Faculty of Agriculture, University of Mataram in May-September 2023. The experiment was arranged based on a factorial Randomized Block Design with six replications (blocks) and two treatment factors, namely plant spacing (J1= 35x20 cm; J2 = 25 x20 cm) and application of mycorrhiza biofertilizer (M0= without; M1= with mycorrhiza). The experimental results showed that the application of mycorrhiza biofertilizer significantly increased plant height, number of leaves, number of productive branches, dry stover weight, weight of filled pods, number of filled pods, number of grains, grain yield per clump, number of root nodules, percentage of AMF colonization on the roots, and number of spores. In contrast, planting distances only affected the number of productive branches, dry stover weight, weight of filled pods, number of filled pods, number of grains, grain yield per clump, weight of 100 seeds, number of root nodules, and the percentage of AMF colonization on the roots, which was higher at planting distance of 25 x 20 cm (J2). However, the interaction between the treatment factors was significant only on number of spores, with the highest number in the M1J2 treatment and the lowest in the M0J1 treatment.